Developing outbound strategic Islamic tour packages of Malaysia: roles of gender and race - Haque, A. K. M. Ahasanul; Ahmed, Faruk; Abdul Razak, Dzuljastri (American Scientific Publishers., 2017)
Gender and race have been issues in every development of human history. Conventional tourism rules out gender and race based on liberalism or secularism or conservatism, whereas Islamic tourism does the same but based on shariah and Islamic principles. Studying these nominal variables are important in developing outbound strategic Islamic tourism services of Malaysia, which allows researchers to create and deliver an enhanced knowledge of a balanced usage of gender and race in this Islamic tourism industry of Malaysia. As a quantitative research approach to explain nominal attributes, 107 of travel and tour agents, and tour operators were observed around Malaysia based on a simple random sample designed from a sampling frame of a list of tourism enterprises considered for a population. Innovativeness, communicativeness, collaboration and cooperation, strategy attitude, strategy intention, and strategy behavior are fixed as dependent variables that have been explained based on mainly gender and race—from which significant differences between endogenous attributes and some sections of nominal ones were captured— and a meaningful interpretation has been proliferated as a help to provide a few effective research, managerial and social implications. The study results would have a values useful for raising a broader sense of these categorical attributes for those administrations in a context like this, and for the readers around and across Malaysia. The effort was employed, for the first time, in this type of context. So perhaps, this can have a vast theoretical understanding of the Islamic tourism conceptualization from the light of nominally inferential research methods.